Propuesta de un método de evaluación editorial de revistas científicas y su aplicación en las revistas de Medicina Veterinaria de América Latina y El Caribe - Arellano-Sota, Carlos; Pérez O., Carmen; Berríos E., Patricio (Avances en Ciencias Veterinarias, 1991)
In this general articles is presented an editorial evaluation method for Veterinary Medicine journals from Latin America and the Caribbean Region with the main purpose to standarise the procedures and to improve the journal's presentation. Key words: Editorial evaluation, Veterinary Medicine journals. Palabras claves: Evaluación editorial, revistas Medicina Veterinaria.